2020
DOI: 10.24093/awej/vol11no1.11
|View full text |Cite
|
Sign up to set email alerts
|

The Challenges and Prospects of Using E-learning among EFL Students in Bisha University

Abstract: This study attempts to find out the challenges students' face in learning English as a foreign language when using E-learning system at University of Bisha. It also investigates whether using E-learning is beneficial to EFL students in their learning English to the degree anticipated. There are many challenges face both teachers and students during use E-learning. These challenges include academic, technological; and administrative challenges. The study sample included 36 teaching staff and 261 EFL students at… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 11 publications
2
53
2
Order By: Relevance
“…This can further assist in maximizing the benefits that comes with the use of technology in education. Electronic learning, otherwise referred to as e-learning was developed by Jay Cross in 1998(Ja'ashan, 2020 and it has continued to metamorphosed up till date. Zhang et al (2004) define "e-learning as technology-based learning in which learning materials are delivered electronically to remote learners via a computer network" (p. 76).…”
Section: Introductionmentioning
confidence: 99%
“…This can further assist in maximizing the benefits that comes with the use of technology in education. Electronic learning, otherwise referred to as e-learning was developed by Jay Cross in 1998(Ja'ashan, 2020 and it has continued to metamorphosed up till date. Zhang et al (2004) define "e-learning as technology-based learning in which learning materials are delivered electronically to remote learners via a computer network" (p. 76).…”
Section: Introductionmentioning
confidence: 99%
“…The research finding also showed that the teacher's difficulties in preparing lesson plans are divided into two major scopes, they are in academic area and technology area (Ja'ashan, 2020;Logan et al, 2021). The teacher found difficulty in aspect 3, especially in selecting learning methods or techniques based on students' characteristics and basic competency as well as learning indicators.…”
Section: Discussionmentioning
confidence: 92%
“…Therefore, teachers are required to be able to create varied learning and by using learning media that support the material (Mulyanto et al, 2020;Oktafiani et al, 2020). Of the many functions of media, one of the main functions of learning media is as an intermediary capable of conveying messages or information so that they can support and have a good impact on the quality of learning provided by educators, such as learning motivation for students, encouragement to learn and emotional feelings students to take part in learning so that they can involve students directly in their use (Buchori et al, 2017;Ja'ashan, 2020). Interactive multimedia is an intermediary tool that conveys messages with collaboration from various elements that can create active learning so that messages from the information conveyed can be well received.…”
Section: Introductionmentioning
confidence: 99%